School Development Strategies in Improving the Quality of Human Resources at Elkisi High School - Indah Indrayani; Nurdyansyah Nurdyansyah; Siti Ruchana (Proceedings of The ICECRS, 2020)
This study aims to determine the school development strategy adopted by Elkisi High School. Quality of Human Resources is the main key / mastermind in the strategy of developing the quality of human resources. Elkisi High School develops school development strategies by implementing a number of strategies, namely developing the quality of human resources, management and institutional modernization. School development is one way to improve the quality of education, in which schools are given the authority and freedom to design, manage and regulate their own schools to become quality and quality schools but still but still bound to National Standard of Education (SNE) adjusted to the curriculum .